Remote education: parents' challenges in teaching during the pandemic - Thalyta Freitas dos Santos Laguna; Tanandra Hermanns; Ana Claudia Pinto da Silva; Liana Nolibos Rodrigues; Josiane Lieberknecht Wathier Abaid (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Objectives: to characterize the teaching-learning process of children in early childhood taught by their parents and/or caregivers in remote educational mode, in different social contexts, during the COVID-19 pandemic. Methods: a bibliographic study was carried out through a qualitative research in three VHL, Lilacs and Scielo databases. The descriptors Children, Pandemic, Caregivers, Distance education and Mental health were used. The sample was composed of 35 materials. Results: it was observed that countries presented problems in its educational system and that their situation also aggravated, such as in Brazil. Schools should try to mitigate the impact of the confinement, based on the recommendations that aim to consolidate what has been learned and interrupt the teaching of new content, eliminating the pressure on parents and guardians who assist students at this time. It is known that there is a lack of preparation of these caregivers, since the vast majority do not have materials or available time, because of home office, making remote learning difficult. The psychological impacts of remote learning - stress, fear, decreased performance and frustration are noticeable in everyone who is involved. Thus, the coping strategy focused on the problem can prevent the worsening of symptoms in mental health. Conclusion: it is expected to promote future reflections according to the theme through Psychology.